Aftermath : The Cultures of the Economic Crisis - Edited by Castells, Manuel ; Caraca, Joao and Cardoso, Gustavo (Oxford Oxford University Press, 2014)
The consequences of the financial crisis may be uncertain, but are sure to reach deep into the body politic, civil society, welfare systems, and reform. This collection of essays by leading international sociologists and social scientists explores the likely outcomes and consequences
Include Tables And Index
Keywords: Global Financial Crisis (2008-2009) -- Social aspects -- Economics--Sociological aspects